Characteristics of cross-functional integration processes: Evidence from Brazilian organizations. Issue 2 (8th August 2016) - Pimenta, Marcio Lopes; da Silva, Andrea Lago; Tate, Wendy L
Abstract : Purpose: – The purpose of this paper is to characterize the cross-functional integration processes between marketing and logistics, while considering five basic elements: boundary spanning activities, integration factors, level of integration, formality/informality and impacts of integration. Design/methodology/approach: – After an extensive literature review, five case studies were performed and in-depth interviews conducted. Both within-case and cross-case analysis was performed to better understand the cross-functional integration processes between marketing and logistics. Findings: – A characterization of cross-functional integration in the form of a managerial framework was proposed. This framework presents the elements in a process view, instead of disconnected parts of the integration processes. The framework and process perspective helps to explain the integration process, the roles and impacts of integration within organizations, while considering cultural formality and informality. Research limitations/implications: – Qualitative data collection and analysis methods cannot achieve amplitude with respect to sampling nor generalize results. In spite of this, the implications revealed by the propositions may be applied not only to Brazilian companies, but organizations in other countries as well, due to the high level of heterogeneity of the sample, and the fact that they represent multinational organizations. Therefore, further research using broad-based survey data could test the correlations between the elements of cross-functional integration processes. Practical implications: – The identification of the cross-functional integration processes within organizations can help managers to facilitate the efforts of integration between marketing and logistics, reducing conflicts and improving business performance. Originality/value: – Case studies focussing specifically on five Brazilian organizations help provide evidence for an initial definition of cross-functional integration processes by analyzing five key elements according to their characteristics and respective roles. This research provides a strong foundation for future broad-based survey research.